Exploratory Factorial Structure of Security Public - Arger Verstapp (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
The aim of this paper is to discuss the scope and limits of social work as a preventive and thanatological device to the politics of fear, nepotism and known as security politic and death. For this purpose, the basic concepts proposed by theories of systems social work exposed. Then, the categories of social fact, social issue, rationalization of another device, social suffering, social ties, social protection, social promotion and intervention about the politics of fear, nepotism and death in order to discuss establish areas of opportunity of Social Work. Finally, a model for social diagnosis of security politic specified